OPTIMASI PEMBUATAN MEMBRAN KOMPOSIT NANOSELULOSA-CHITOSAN DARI SCOBY KOMBUCHA - Mutiara K Muharam, Salsabila
Packaging is one important aspect that must be considered in the food industry. Packaging has an important role to protect food from environmental damage, such as chemical and physical damage. Food packaging is known to have evolved along with human development. Food packaging that is commonly used today has raw materials in the form of paper and plastic. However, the use of plastics as food packaging is becoming an environmental problem, where plastic is difficult to degrade. This condition encourages researchers to develop environmentally friendly compounds that can be applied as food packaging. Symbiotic Culture of Bacteria and Yeast (SCOBY) is one of the byproducts of cellulose polymer produced by bacteria in kombucha fermentation process. SCOBY is considered to be potentially developed into food packaging because it has a flexible texture, has a short production time, and environmentally friendly. SCOBY development into membrane nanocellulose as food packaging can be done by changing the structure of SCOBY first into nanocellulose. In this research, optimization of enzyme nanocellulose making is further developed into cellulose fiber by using Electrospinning method. Optimization of nanocellulose preparation was carried out enzymatically using the crude extract of cellulase enzyme produced by Bacillus sp. The study was started by determining optimum inoculum age and optimum cellulase production time at Bacillus sp first. The optimization variation in this research is optimization of volume enzyme and incubation time of enzyme on cellulose. Nanocellulose that has been formed, then analyzed using PSA, SEM and FTIR to determine the best variations in the manufacture of nanoselulosa. The best nanocellulose was composite with chitosan and starch into nanocellulose-chitosan membrane. Characterization of membrane was tested using SEM and water absorption test. The results showed that the age of optimum inoculum of Bacillus sp growth was at 12 hours and the optimum cellulase production time of Bacillus sp was at 36 hours incubation time inoculum with FPAse activity of 2.83 U / ml and CMCase activity of 2.92 U / ml. The optimum result of enzyme nanocellulose making showed the change of cellulose particle size with the initial size of 738nm to be 60 - 191nm. The result was obtained by variation of enzyme count of 2: 3 (v / w) with incubation time for 4 days at 50oC with agitation 200 rpm. The nanocellulose has a crystaline structure based on the SEM results, and FTIR results show that the enzyme-treated nanocellulose has a lower wave peak value than the SCOBY sample. Nanocellulose-chitosan composite membranes are known to have smaller membrane pores than pores on chitosan membranes. Smaller pore size has been shown to affect the speed of water absorption in the membrane, where membranes with higher nanocellulose concentrations produce smaller membrane pores that have a slower absorption capacity. Based on these results, it can be concluded that the optimum amount of enzyme that can be used to make nanoselulose is 2: 3 (v / w) SCOBY with incubation time for 4 days. The obtained nanoselulose size is 60nm, with a crystaline nanoselulose structure. Cellulose fibers produced from electrospinning have not been established due to electrospinning conditions that are not yet optimum. Nanocellulose-chitosan composite membrane has the smallest pore measuring 760nm with a water absorption speed of 95 seconds/0,05ml.